Large-Area Epitaxial Monolayer MoS2 - Dumcenco, Dumitru; Ovchinnikov, Dmitry; Marinov, Kolyo; Lazić, Predrag; Gibertini, Marco; Marzari, Nicola; Sanchez, Oriol Lopez; Kung, Yen-Cheng; Krasnozhon, Daria; Chen, Ming-Wei; Bertolazzi, Simone; Gillet, Philippe; et al. (ACS nano, 2015)
Two-dimensional semiconductors such as MoS2 are an emerging material family with wide-ranging potential applications in electronics, optoelectronics, and energy harvesting. Large-area growth methods are needed to open the way to applications. Control over lattice orientation during growth remains a challenge. This is needed to minimize or even avoid the formation of grain boundaries, detrimental to electrical, optical, and mechanical properties of MoS2 and other 2D semiconductors. Here, we report on the growth of high-quality monolayer MoS2 with control over lattice orientation. We show that the monolayer film is composed of coalescing single islands with limited numbers of lattice orientation due to an epitaxial growth mechanism. Optical absorbance spectra acquired over large areas show significant absorbance in the high-energy part of the spectrum, indicating that MoS2 could also be interesting for harvesting this region of the solar spectrum and fabrication of UV-sensitive photodetectors. Even though the interaction between the growth substrate and MoS2 is strong enough to induce lattice alignment via van der Waals interaction, we can easily transfer the grown material and fabricate devices. Local potential mapping along channels in field-effect transistors shows that the single-crystal MoS2 grains in our film are well connected, with interfaces that do not degrade the electrical conductivity. This is also confirmed by the relatively large and length-independent mobility in devices with a channel length reaching 80 μm.